High-signal intensity in the dentate nucleus and globus pallidus on unenhanced T1-weighted emages: evaluation of the macrocyclic gadolinium-based contrast agent Gadobutrol - Radbruch, Alexander; Weberling, Lukas D.; Kieslich, Pascal J.; Hepp, Johanna; Vollmuth, Philipp; Wick, Wolfgang; Schlemmer, Heinz-Peter; Bendszus, Martin (Investigative radiology, 2015)
OBJECTIVE: The aim of this study was to compare changes in the signal intensity (SI) ratio of the dentate nucleus (DN) to the pons, DN to cerebrospinal fluid (CSF), and globus pallidus (GP) to thalamus on unenhanced T1-weighted magnetic resonance imaging (MRI) scans after serial injections of the macrocyclic gadolinium-based contrast agent gadobutrol. MATERIALS AND METHODS: Thirty patients who had received at least 5 MRI examinations (plus an additional last MRI for reference) with the exclusive use of gadobutrol, resulting in a total cumulative dose of 54.1 ± 30.4 mL gadobutrol, were analyzed retrospectively. Signal intensity ratio differences were calculated for DN-to-pons, DN-to-CSF, and GP-to-thalamus ratios by subtracting the SI ratio at the first MRI from the SI ratio at the last MRI scan. One-sample t tests were employed to examine if they differed from 0. Regression and correlational analyses were performed to examine whether the SI ratio differences were predicted by a number of control variables. RESULTS: Signal intensity ratio differences did not differ significantly from 0, neither for the DN-to-pons ratio (-0.0035 ± 0.0476, P = 0.69), the DN-to-CSF ratio (-0.0539 ± 0.3217, P = 0.37), nor the GP-to-thalamus ratio (-0.0020 ± 0.0211, P = 0.60). None of the control variables predicted changes in SI ratios. CONCLUSIONS: In contrast to a recently published study, we did not find signal increases in the DN or in the GP after serial injections of gadobutrol, even though the total dose applied here was considerably larger than in the respective study. This finding adds further support to the hypothesis that the molecular structure of a gadolinium-based contrast agent as either macrocyclic or linear is a crucial factor for its potential to cause gadolinium deposition in the brain. Future studies should further assess this hypothesis by additional animal investigations as well as histopathological and clinical correlation studies.